Hardware-software complex for studying the effect of air composition on the aerodynamic parameters of nasal breathing - Аврунін, О. Г.; Носова, Я. В.; Шушляпіна, Н. О.; Худаєва, С. А.; Ибрагим Юнус Абделхамид (RS Global, 2019)
Hardware-software complex for studying the effect of air composition on the aerodynamic parameters of nasal breathing is described.
Keywords: hardware-software complex; nasal breathing; air flow; nasal aerodynamic